Carbon film current collector and preparation method and application thereof
By using carbon film current collectors prepared by graphene oxide and tetraethyl titanate, the problems of low conductivity and insufficient mechanical strength of carbon paper current collectors in aqueous ion batteries are solved, and the performance and stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202410195832.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-02-22
AI Technical Summary
In the existing water-based ion batteries, carbon paper, as the current collector, has problems such as low conductivity, poor ion conductivity and low mechanical strength, which limits the performance of the battery.
A carbon film current collector composed of graphene oxide and tetraethyl titanate is prepared by crosslinking and controlling the proportion of materials to prepare a carbon film current collector with stable structure, good conductivity and high mechanical strength.
The conductivity, ion conductivity and mechanical strength of the carbon film current collector are improved, and the cycle stability and electrochemical properties of the aqueous ion battery are enhanced.
Smart Images

Figure CN118054018B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aqueous ion batteries, and in particular to a carbon film current collector and a preparation method and application thereof. Background Art
[0002] Fossil fuels are the main energy source for human beings at this stage. These fuels are non-renewable resources. Their non-renewable nature also indicates that human beings’ use of these resources is ultimately limited, and the large-scale development and use of these resources will cause great damage to the natural environment. The demand for clean and renewable energy is becoming increasingly urgent. Batteries are devices that convert chemical energy into electrical energy and are devices that humans will vigorously develop in the future.
[0003] Currently, lithium-ion batteries dominate the market, but the scarcity of lithium resources and the fact that organic electrolytes are usually toxic and flammable have limited the development of lithium-ion batteries. In the process of searching for alternatives to lithium-ion batteries, people have discovered aqueous electrolytes that have lower resistance, greater conductivity, and greater power density than organic electrolytes.
[0004] Carbon paper is often used as a current collector for positive and negative electrode materials of aqueous batteries, but it has low electrical conductivity, poor ion conductivity and low mechanical strength. Therefore, it is very meaningful and promising to study a current collector that can be used in aqueous batteries. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a carbon film current collector to solve the problems raised in the above background technology.
[0006] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:
[0007] A carbon film current collector comprises graphene oxide and tetraethyl titanate; the mass ratio of the graphene oxide to tetraethyl titanate is 1:(0.01-0.1).
[0008] Preferably, the mass ratio of graphene oxide to tetraethyl titanate is 1:(0.02-0.08).
[0009] Another object of the embodiment of the present invention is to provide a method for preparing the above-mentioned carbon film current collector, which comprises the following steps:
[0010] dispersing graphene oxide and tetraethyl titanate in a solvent to obtain a colloidal solution;
[0011] The colloidal solution is coated on a substrate and then dried to form a thin film to obtain the carbon film current collector.
[0012] Preferably, the solvent is an organic solvent.
[0013] Preferably, the organic solvent is one or more of anhydrous ethanol, ethylene glycol and N,N-dimethylformamide.
[0014] Preferably, the coating thickness is 40-120 μm.
[0015] Preferably, the temperature of the drying treatment is 200-300°C.
[0016] Another object of an embodiment of the present invention is to provide a carbon film current collector prepared by the above preparation method.
[0017] Another object of an embodiment of the present invention is to provide an application of the above-mentioned carbon film current collector in an aqueous ion battery.
[0018] Another object of an embodiment of the present invention is to provide an aqueous ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the positive electrode and / or the negative electrode comprises the above-mentioned carbon film current collector.
[0019] The embodiment of the present invention cross-links tetraethyl titanate and graphene oxide, and controls the mass ratio of the two materials to obtain a carbon film current collector with stable structure, good electrical conductivity, good ion conductivity, and high mechanical strength. The preparation method of the carbon film current collector is simple and convenient, low cost, and green and environmentally friendly. The positive and negative active materials are coated on the carbon film current collector, and the assembled aqueous ion battery has the advantages of good cycle stability and excellent electrochemical performance, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A process flow chart of a method for preparing a carbon film current collector provided by an embodiment of the present invention;
[0021] Figure 2 The polarization curve diagram of the aqueous ion battery assembled from Comparative Example 1 and Application Example 1 of the present invention;
[0022] Figure 3 This is a cycle performance diagram of the aqueous ion battery assembled from Comparative Example 1 and Application Example 1 of the present invention at a current of 0.2C. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In one embodiment of the present invention, a carbon film current collector is provided, which comprises graphene oxide and tetraethyl titanate; the mass ratio of graphene oxide to tetraethyl titanate is 1:(0.01-0.1).
[0025] The embodiment of the present invention cross-links tetraethyl titanate with graphene oxide to obtain a carbon film current collector with stable structure, good conductivity and high mechanical strength. In particular, by adding tetraethyl titanate material, the embodiment of the present invention can make the carbon film current collector have better peel strength and ion conductivity; in addition, by adjusting the ratio of the two materials, the embodiment of the present invention can make the prepared carbon film current collector have the best peel strength and ion conductivity.
[0026] In a preferred embodiment of the present invention, the mass ratio of graphene oxide to tetraethyl titanate is 1:(0.02-0.08).
[0027] like Figure 1 As shown, in another embodiment of the present invention, a method for preparing a carbon film current collector is also provided, which comprises the following steps:
[0028] S1, dispersing graphene oxide and tetraethyl titanate in a solvent to obtain a colloidal solution;
[0029] S2. Applying the colloidal solution onto a substrate, and then drying and rolling the solution to form a thin film to obtain a carbon film current collector.
[0030] Specifically, the substrate may be glass; the solvent is an organic solvent; preferably, the organic solvent is one or more of anhydrous ethanol, ethylene glycol and N,N-dimethylformamide, but is not limited thereto.
[0031] It should be noted that the amount of the solvent used can be adjusted according to the state of the colloidal solution, so as to obtain a colloidal solution that is most conducive to coating.
[0032] In a preferred embodiment of the present invention, in order to make the carbon film current collector have better mechanical strength, the coating thickness is 40-120 μm.
[0033] In a preferred embodiment of the present invention, the drying process is carried out at a temperature of 200-300° C. and for a time of 1-3 hours.
[0034] The embodiment of the present invention can prepare a carbon film current collector with stable structure, good conductivity and high mechanical strength by controlling the mass ratio of graphene oxide and tetraethyl titanate, coating thickness and drying temperature. The preparation method of the carbon film current collector has simple reaction conditions, simple steps, simple and convenient operation and low cost.
[0035] In another embodiment of the present invention, there is also provided an application of the above-mentioned carbon film current collector in an aqueous ion battery.
[0036] In another embodiment of the present invention, an aqueous ion battery is provided, comprising a positive electrode, a negative electrode and a separator, wherein the positive electrode and / or the negative electrode comprises the above-mentioned carbon film current collector.
[0037] In a preferred embodiment of the present invention, the positive electrode includes a carbon-coated aluminum foil current collector and a positive electrode active material coated on the carbon-coated aluminum foil current collector; the positive electrode active material can be a positive electrode material conventionally used in the art, for example, it can be selected from one or more of lithium manganese oxide, lithium iron phosphate and ternary lithium, but is not limited thereto.
[0038] In a preferred embodiment of the present invention, the negative electrode includes a carbon-coated aluminum foil current collector and a negative electrode active material coated on the carbon-coated aluminum foil current collector; the negative electrode active material can be a negative electrode material conventionally used in the art, for example, can be selected from hard carbon and / or sodium titanium phosphate, but is not limited thereto.
[0039] In a preferred embodiment of the present invention, the separator may be selected from one or more of glass fiber, polyethylene and mixed cellulose, but is not limited thereto.
[0040] The aqueous ion battery assembled by coating the positive and negative electrode active materials on the carbon film current collector in the embodiment of the present invention has the advantages of good cycle stability and excellent electrochemical performance, and has broad application prospects.
[0041] The following embodiments are some specific implementation cases and application cases of the present invention in practical applications, but are not limited thereto.
[0042] Embodiment 1: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0043] (1) Weighing 10 g of graphene oxide and 0.1 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0044] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 80 μm, and then dried at 200° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B1.
[0045] Embodiment 2: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0046] (1) Weighing 10 g of graphene oxide and 0.2 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0047] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 80 μm, and then dried at 200° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B2.
[0048] Embodiment 3: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0049] (1) Weighing 10 g of graphene oxide and 0.5 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0050] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 80 μm, and then dried at 200° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B3.
[0051] Embodiment 4: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0052] (1) Weighing 10 g of graphene oxide and 1 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0053] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 80 μm, and then dried at 200° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B4.
[0054] Embodiment 5: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0055] (1) Weighing 10 g of graphene oxide and 0.1 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0056] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 100 μm, and then dried at 200° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B5.
[0057] Embodiment 6: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0058] (1) Weighing 10 g of graphene oxide and 0.1 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0059] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 120 μm, and then dried at 200° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B6.
[0060] Embodiment 7: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0061] (1) Weighing 10 g of graphene oxide and 0.1 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0062] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 80 μm, and then dried at 250° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B7.
[0063] Embodiment 8: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0064] (1) Weighing 10 g of graphene oxide and 0.1 g of tetraethyl titanate respectively, dispersing them in 10 mL of N,N-dimethylformamide to obtain a colloidal solution;
[0065] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 80 μm, and then dried at 300° C. for 2 h to form a thin film, thereby obtaining a carbon film current collector, which is denoted as B8.
[0066] Embodiment 9: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0067] (1) Weighing 10 g of graphene oxide and 0.2 g of tetraethyl titanate respectively, dispersing them in 10 mL of anhydrous ethanol to obtain a colloidal solution;
[0068] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 40 μm, and then dried at 250° C. for 1 h to form a thin film, thereby obtaining a carbon film current collector.
[0069] Embodiment 10: This embodiment provides a method for preparing a carbon film current collector, which comprises the following steps:
[0070] (1) Weighing 10 g of graphene oxide and 0.8 g of tetraethyl titanate respectively, dispersing them in 10 mL of ethylene glycol to obtain a colloidal solution;
[0071] (2) The colloidal solution is coated onto a glass substrate with a coating thickness of 120 μm, and then dried at 250° C. for 3 h to form a thin film, thereby obtaining a carbon film current collector.
[0072] Application Example 1: This application example provides an aqueous ion battery, the preparation method of which includes the following steps:
[0073] (1) Preparation of positive electrode sheet: lithium manganese oxide material, carbon black and polyvinylidene fluoride (PVDF) were mixed uniformly in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added to mix to obtain a slurry, which was then uniformly coated on the carbon-coated aluminum foil current collector B3 obtained in Example 3 to obtain a positive electrode sheet; wherein the loading amount of the active substance lithium manganese oxide material is 1.0-2.0 mg cm -2 .
[0074] (2) Preparation of negative electrode sheet: Sodium titanium phosphate material, carbon black and PVDF were mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP was added to mix to obtain a slurry, which was then evenly coated on the carbon-coated aluminum foil current collector B3 obtained in Example 3 to obtain a negative electrode sheet; wherein the loading amount of the active substance sodium titanium phosphate material was 1.0-2.0 mg cm -2 .
[0075] (3) Preparation of glass fiber diaphragm: Cut GF-A glass fiber into 18 mm discs for later use.
[0076] (4) Preparation of battery: The positive electrode sheet, negative electrode sheet and glass fiber separator prepared above were assembled into an aqueous ion battery using a 2016 battery shell at room temperature, and the polarization curve (Tafel curve) and cycle performance at 0.2C current were measured. The results are as follows: Figure 2 and Figure 3 shown.
[0077] Comparative Example 1: The method provided in Application Example 1 was used, except that commercial carbon paper was used as the current collector of the positive and negative electrode materials to assemble an aqueous ion battery, and its polarization curve (Tafel curve) and cycle performance at 0.2C current were measured. The results are as follows: Figure 2 and Figure 3 shown.
[0078] in, Figure 2 The Tafel curve of the aqueous ion battery assembled from Comparative Example 1 and Application Example 1 is shown in FIG. Figure 2 It can be seen that the corrosion potential of the aqueous ion battery assembled in Comparative Example 1 is -0.55V (vs.Hg / Hg2Cl2), while the corrosion potential of the aqueous ion battery assembled in Application Example 1 is -0.33V (vs.Hg / Hg2Cl2). It can be seen that commercial carbon paper is very easy to corrode, and the aqueous ion battery assembled with the carbon film current collector made of graphene oxide in Application Example 1 of the present invention has good corrosion resistance.
[0079] Figure 3 The cycle performance diagram of the aqueous ion battery assembled into Comparative Example 1 and Application Example 1 at 0.2C current is shown in FIG. Figure 3 It can be seen that the discharge capacity of the aqueous ion battery assembled in Application Example 1 is stable at 71 mAh g -1 , while the discharge capacity of the aqueous ion battery assembled in Comparative Example 1 is 58 mAh·g -1 It can be seen that the carbon film current collector provided by the embodiment of the present invention greatly improves the cycle stability and electrochemical performance of the battery.
[0080] Application Example 2: This application example provides an aqueous ion battery, the preparation method of which includes the following steps:
[0081] (1) Preparation of positive electrode sheet: lithium manganese oxide material, carbon black and polyvinylidene fluoride (PVDF) were mixed uniformly in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added to mix to obtain a slurry, which was then uniformly coated on the carbon-coated aluminum foil current collector B1 obtained in Example 1 to obtain a positive electrode sheet; wherein the loading amount of the active substance lithium manganese oxide material is 1.0-2.0 mg cm -2 .
[0082] (2) Preparation of negative electrode sheet: Sodium titanium phosphate material, carbon black and PVDF were mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP was added to mix to obtain a slurry, which was then evenly coated on the carbon-coated aluminum foil current collector B1 obtained in Example 1 to obtain a negative electrode sheet; wherein the loading amount of the active substance sodium titanium phosphate material was 1.0-2.0 mg cm -2 .
[0083] (3) Preparation of glass fiber diaphragm: Cut GF-A glass fiber into 18 mm discs for later use.
[0084] (4) Preparation of battery: The positive electrode sheet, negative electrode sheet and glass fiber separator prepared above were assembled into an aqueous ion battery using a 2016 battery shell at room temperature.
[0085] Application Example 3: This application example provides an aqueous ion battery, the preparation method of which includes the following steps:
[0086] (1) Preparation of positive electrode sheet: lithium manganese oxide material, carbon black and polyvinylidene fluoride (PVDF) were mixed uniformly in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added to mix to obtain a slurry, which was then uniformly coated on the carbon-coated aluminum foil current collector B2 prepared in Example 2 to obtain a positive electrode sheet; wherein the loading amount of the active substance lithium manganese oxide material is 1.0-2.0 mg cm -2 .
[0087] (2) Preparation of negative electrode sheet: Sodium titanium phosphate material, carbon black and PVDF were mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP was added to mix to obtain a slurry, which was then evenly coated on the carbon-coated aluminum foil current collector B2 prepared in Example 2 to obtain a negative electrode sheet; wherein the loading amount of the active substance sodium titanium phosphate material was 1.0-2.0 mg·cm -2 .
[0088] (3) Preparation of glass fiber diaphragm: Cut GF-A glass fiber into 18 mm discs for later use.
[0089] (4) Preparation of battery: The positive electrode sheet, negative electrode sheet and glass fiber separator prepared above were assembled into an aqueous ion battery using a 2016 battery shell at room temperature.
[0090] The aqueous ion batteries prepared in the comparative example 1 and application examples 1-3 were subjected to peel strength and battery electrochemical impedance tests, and the results are shown in Table 1.
[0091] Table 1
[0092] Test items Peel strength (N / cm) Solution resistance Rs(Ω) Charge transfer resistance Rct(Ω) Comparative Example 1 6.1 3.61 168.3 Application Example 1 14.9 3.02 138.4 Application Example 2 13.2 2.94 121.2 Application Example 3 14.1 2.75 90.8
[0093] From the above content and the data in Table 1, it can be seen that the peel strength of the aqueous ion battery prepared using the carbon film current collector prepared in the embodiment of the present invention is as high as 14.9 N / cm, which is much greater than the peel strength of the aqueous ion battery prepared using commercial carbon paper in Comparative Example 1, indicating that the carbon film current collector prepared using tetraethyl titanate cross-linked graphene oxide in the present invention has better mechanical strength; at the same time, the Rs and Rct of the aqueous ion battery prepared using the carbon film current collector prepared in the embodiment of the present invention are both lower than those of the aqueous ion battery prepared using commercial carbon paper in Comparative Example 1, indicating that the carbon film current collector prepared in the embodiment of the present invention has better electrical conductivity and ion conductivity.
[0094] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.
Claims
1. A method for preparing a carbon film current collector, characterized in that: The following steps are involved: Dispersing graphene oxide and tetraethyl titanate in a solvent to obtain a colloidal solution; the mass ratio of graphene oxide to tetraethyl titanate is 1:(0.01-0.1); The colloidal solution is coated on a substrate and then dried to form a thin film to obtain the carbon film current collector.
2. The method for preparing a carbon film current collector according to claim 1, characterized in that: The mass ratio of the graphene oxide to tetraethyl titanate is 1:(0.02-0.08).
3. The method for preparing a carbon film current collector according to claim 1, characterized in that: The solvent is an organic solvent.
4. The method for preparing a carbon film current collector according to claim 3, characterized in that: The organic solvent is one or more of anhydrous ethanol, ethylene glycol and N,N-dimethylformamide.
5. The method for preparing a carbon film current collector according to claim 1, characterized in that: The coating thickness is 40-120 μm.
6. The method for preparing a carbon film current collector according to claim 1, characterized in that: The temperature of the drying process is 200-300°C.
7. A carbon film current collector prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the carbon film current collector as claimed in claim 7 in an aqueous ion battery.
9. An aqueous ion battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The positive electrode and / or the negative electrode comprises the carbon film current collector according to claim 7.
Citation Information
Patent Citations
Graphene composite negative current collector, preparation method thereof and lithium ion battery
CN103579632A
Conductive fibers and preparation method and application thereof
CN111778575A